The impact of peacekeeping mission on physical and psychological health among Pakistani troops deployed in Democratic Republic of Congo during the COVID Pandemic : An Original article - mehreen; Huma Babar; Sofia kousar; Sonia kanwal (Journal of Peace, Development and Communication, 2021)
The impact of peacekeeping mission on physical and mental health among Pakistani troops deployed in Democratic Republic of Congo during the COVID 19 Pandemic. ABSTRACT This study has been conducted to examine the impact of deployment in mission area on physical, mental and social health and wellbeing of the peacekeepers. This was a cross sectional analytical study of about 12 months starting from Jan 2020 to Jan 2021. The data was collected from three phases of the time span: initial deployment, mid deployment, Post deployment. The health record of the troops had stated that despite of taking anti-malarial prophylaxis 16% troops still got malaria positive, while 55% of troops suffered allergic rhinitis. The Psychological score was calculated by self-reported Stress, Anxiety and Depression level measured by DASS-21. A negligible number of cases has been found in psychological distress: 1.3% has been found in mild stress. 1.8% in mild depression and 0.5% in anxiety. The military steadfastness of peacekeepers was predicted with military hardiness scale and was analyzed with Pearson correlation by SPSS 22. It has been revealed that troops with better military robustness have enhanced physical and psychological health. Military toughness and resilience, good social support and pre deployment preparedness, play a significant role in maintaining good psychological health. As the deployment length increases, the probability of detrimental health effects also rises.